2015
DOI: 10.1210/en.2015-1866
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte-Specific Disruption of CD36 Attenuates Fatty Liver and Improves Insulin Sensitivity in HFD-Fed Mice

Abstract: CD36/FAT (fatty acid translocase) is associated with human and murine nonalcoholic fatty liver disease, but it has been unclear whether it is simply a marker or whether it directly contributes to disease pathogenesis. Mice with hepatocyte-specific deletion of Janus kinase 2 (JAK2L mice) have increased circulating free fatty acids (FAs), dramatically increased hepatic CD36 expression and profound fatty liver. To investigate the role of elevated CD36 in the development of fatty liver, we studied two models of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
292
4
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(329 citation statements)
references
References 43 publications
26
292
4
7
Order By: Relevance
“…Despite the well-documented function of CD36 in fatty acid uptake (41) and several reports that associate hepatic CD36 signaling with an increased risk of developing liver steatosis (3,5,6,8,42), we showed that overexpression of CD36 in the livers of our transgenic mice did not worsen metabolic functions but rather protected the mice from the detrimental metabolic changes caused by HFD feeding and prolonged fasting. The antisteatotic effect of CD36 is consistent with a report that whole-body CD36 ablation exacerbated hepatic steatosis in the ob/ob background (10) but is contrary to a recent study showing that liver-specific knockout of CD36 reduced the liver lipid content when mice were challenged with HFD (42).…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Despite the well-documented function of CD36 in fatty acid uptake (41) and several reports that associate hepatic CD36 signaling with an increased risk of developing liver steatosis (3,5,6,8,42), we showed that overexpression of CD36 in the livers of our transgenic mice did not worsen metabolic functions but rather protected the mice from the detrimental metabolic changes caused by HFD feeding and prolonged fasting. The antisteatotic effect of CD36 is consistent with a report that whole-body CD36 ablation exacerbated hepatic steatosis in the ob/ob background (10) but is contrary to a recent study showing that liver-specific knockout of CD36 reduced the liver lipid content when mice were challenged with HFD (42).…”
Section: Discussioncontrasting
confidence: 93%
“…The antisteatotic effect of CD36 is consistent with a report that whole-body CD36 ablation exacerbated hepatic steatosis in the ob/ob background (10) but is contrary to a recent study showing that liver-specific knockout of CD36 reduced the liver lipid content when mice were challenged with HFD (42). Future studies are necessary to explain the discrepancies in the fatty liver phenotypes between the whole-body and liver-specific CD36 knockout models.…”
Section: Discussionsupporting
confidence: 86%
“…Although global Cd36 knockout does not protect against high fructose-induced hepatic steatosis (Hajri, et al 2002) or prevent fatty liver in ob/ob mice (Nassir, et al 2013), a more recent report supports a liver-specific role of Cd36 in FA uptake. Specifically, congenital liver-specific Cd36 knockout reduced steatosis in liver-specific Jak2 knockout mice that led to an increase in plasma NEFA (Wilson, et al 2015). Also in that same study, liver-specific Cd36 knockout mice with intact hepatic Jak2, dramatically reduced HF-diet induced steatosis that was associated with a reduction in hepatic FA uptake as measured by hepatic accumulation of BODIPY-FA in vivo (Wilson et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperinsulinemia alone can stimulate hepatic Cd36 expression, and is suggested as a primary mechanism driving hepatic lipid accumulation (Steneberg et al 2015). Hepatic-specific knockout of Cd36 protects mice from high-fat diet-induced fatty liver and insulin resistance, supporting the hypothesis that increased hepatic lipid uptake is critical for the development of hepatic triglyceride accumulation (Wilson et al 2016). Hepatic lipoprotein lipase (LPL) expression and activity are also increased in high-fat diet-fed mice and obese individuals, offering another mechanism for increased hepatic lipid uptake in fatty liver disease (Pardina et al 2009, Ahn et al 2011.…”
Section: Adipose Tissue Lipolysis and Hepatic Lipid Uptakementioning
confidence: 92%